2012
DOI: 10.1016/j.neuropsychologia.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent dopaminergic modulation of reward-based learning in Parkinson's disease

Abstract: Learning to select optimal behavior in new and uncertain situations is a crucial aspect of living and requires the ability to quickly associate stimuli with actions that lead to rewarding outcomes. Mathematical models of reinforcement-based learning to select rewarding actions distinguish between (1) the formation of stimulus–action–reward associations, such that, at the instant a specific stimulus is presented, it activates a specific action, based on the expectation that that particular action will likely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
1
17
2
Order By: Relevance
“…Thus, although we cannot delineate the exact contribution of altered dopaminergic tone to the FRN, our results strongly suggest that any impairment in dopaminergic modulation, both under and over activation, would likely result in inadequate expectation signaling and thus the FRN response found here. Future studies may address this issue using drug-naive patients, although previous studies have indicated little effect of medication on reward tasks [ 42 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although we cannot delineate the exact contribution of altered dopaminergic tone to the FRN, our results strongly suggest that any impairment in dopaminergic modulation, both under and over activation, would likely result in inadequate expectation signaling and thus the FRN response found here. Future studies may address this issue using drug-naive patients, although previous studies have indicated little effect of medication on reward tasks [ 42 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many reinforcement learning paradigms, only overt actions are associated to reward or punishment outcomes (i.e., instrumental learning) (Frank, Seeberger & O'Reilly, 2004; O'Doherty, 2004; van Wouwe, Ridderinkhof, Band, van den Wildenberg & Wylie, 2012). However, in many situations, refraining from action is necessary for reward acquisition and punishment avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in order to maximize learning, is crucial the ability to associate stimuli with actions that lead to rewarding outcomes (van Wouwe et al, 2012 ). Therefore, in the following sections, we will explore the impact of DRT on learning and reward.…”
Section: Rehabilitation In Pd: Key Points For Effectivenessmentioning
confidence: 99%
“…Although the basal ganglia are traditionally known to contribute to motor function, more recently they have been shown to be engaged in several types of learning, including habit formation, procedural skill learning, and reward-based decision-learning (van Wouwe et al, 2012 ). Therefore, involving the disruption of basal ganglia, PD provides an informative naturalistic model for understanding the role of dopamine in reward and learning.…”
Section: The Impact Of Drt On Learning and Rewardmentioning
confidence: 99%